2021
DOI: 10.1108/gkmc-03-2021-0040
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing and self-efficacy in an EFL context: the mediating effect of creativity

Abstract: Purpose As demonstrated in the literature, teachers’ knowledge sharing, self-efficacy and creativity display certain levels of cause-and-effect and correlational connections from different perspectives. Nonetheless, few studies, if any, have been reported on the interplay of these three concepts in the context of the language classroom. As such, this study aims to test a structural model of English as a foreign language (EFL) teachers’ knowledge sharing, self-efficacy and creativity and specifically to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 97 publications
1
3
0
Order By: Relevance
“…Research conducted by Huang et al, (2019b) states that teachers' creative self-efficacy mediates the relationship between creative role identity and teachers' positive implementation attitudes, and process-focused self-efficacy was found to be significantly related to teachers' positive implementation attitudes, while self-efficacy which focuses on the product is not significantly related to the teacher's positive implementation attitude. this research is in line with the results of research from Parhamnia et al, (2022) which states that creativity is a mediator of knowledge sharing and self-efficacy in the context of learning English.…”
Section: Discussionsupporting
confidence: 89%
“…Research conducted by Huang et al, (2019b) states that teachers' creative self-efficacy mediates the relationship between creative role identity and teachers' positive implementation attitudes, and process-focused self-efficacy was found to be significantly related to teachers' positive implementation attitudes, while self-efficacy which focuses on the product is not significantly related to the teacher's positive implementation attitude. this research is in line with the results of research from Parhamnia et al, (2022) which states that creativity is a mediator of knowledge sharing and self-efficacy in the context of learning English.…”
Section: Discussionsupporting
confidence: 89%
“…The mediating effect of knowledge sharing in the relationship between EL and nursing team creativity was significant. This result is like that of Parhamnia et al, 38 probably because EL demonstrates a viable vision by constructing a challenge and inviting members to work toward that goal. It motivates team members by building commitment and a clear path to remove obstacles in their work 39 .…”
Section: Discussionsupporting
confidence: 68%
“…In the research of Yang and Cheng (2009), it is emphasized that the KSB exhibited in the field of information technology has a positive impact on creative self-efficacy. In their study, (Parhamnia, Farahian and Rajabi, 2022;Sun, Hong and Ye, 2022) found that KSB had a positive impact on CSE. Considering this knowledge, it is possible to make the assumption that workers will improve their CSE as a result of the new knowledge they learn…”
Section: Knowledge Sharing Behavior and Creative Self-efficacymentioning
confidence: 95%